Kesenjangan Literasi Keuangan Remaja Kota Gorontalo Berdasarkan Status Ekonomi: Miskin, Hampir Miskin, dan Berpenghasilan Tinggi - Rierind Koniyo; Juniarti, Gita Juniarti; Fatmawaty Damiti (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This descriptive qualitative research analyzed the financial literacy gap among six adolescents in Gorontalo City. They are divided into three groups, namely poor families, families on the verge of poverty, and rich families. This study uses a narrative inquiry approach by looking at the experiences of adolescents and their families in managing finances. The purpose of this study is to show adolescents' practical experience in financial management behavior. This experience became the basis for analyzing adolescent financial literacy in each group. The results of the study show that there are different needs for financial literacy, ranging from the need to survive to efforts to accumulate wealth. Teenagers from poor families tend to implement cost savings and manage money on a daily basis. Meanwhile, teens from wealthy families show a broader understanding, not only managing daily needs, but also starting to learn to plan long-term goals. They are encouraged to set savings targets together in order to realize their dreams and understand the basics of asset management. Groups on the brink of poverty are in the middle and need literacy about financial resilience and the ability to buy goods with the best value. The biggest risk for the wealthy group is impulse buying due to social pressures. Therefore, financial literacy education needs to be differentiated according to the economic conditions of students, ranging from survival to investment and insurance.